2004
DOI: 10.1002/mmce.20022
|View full text |Cite
|
Sign up to set email alerts
|

EM design of broadband RF multiport toggle switches

Abstract: Radio frequency (RF) MEMS is an emerging sub-area of MEMS technology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Special switch designs for high-power handling have been proposed in recent years [12]- [16]. Active opening mechanisms [17], including a so-called toggle switch design which relies on a push-pull mechanism [18], are more suitable for high-power applications than those designs entirely relying on passive opening forces [19]. A special metal-contact design employing ball grid array dimples demonstrates RF power handling more than 1 W and achieves hot switching in excess of 100 million cycles [20].…”
Section: Introductionmentioning
confidence: 99%
“…Special switch designs for high-power handling have been proposed in recent years [12]- [16]. Active opening mechanisms [17], including a so-called toggle switch design which relies on a push-pull mechanism [18], are more suitable for high-power applications than those designs entirely relying on passive opening forces [19]. A special metal-contact design employing ball grid array dimples demonstrates RF power handling more than 1 W and achieves hot switching in excess of 100 million cycles [20].…”
Section: Introductionmentioning
confidence: 99%
“…The use of an arc‐suppression circuit was also reported to enable arcless operation of microrelays for high power applications 16. Actuation‐assisted release mechanisms 5, 17, 18 have also been actively studied to address stiction related failures in MEMS contact switches.…”
Section: Introductionmentioning
confidence: 99%
“…The switch membrane was composed of a 2 urn PECVD silicon oxide and suspended with a height of 2.5 fim above the substrate, being connected to the substrate on four anchors though a folded spring structure. DaimlerChrysler Research Center, Germany, developed a toggle switch as shown in Figure 9 which relies on a push-pull mechanism in 2002-2005 [26], [27], [28]. The…”
Section: Series Mems Switch Developedmentioning
confidence: 99%
“…Here, // = 1 for a flat diaphragm while n >\ for a corrugated diaphragm, which is determined by Equation 20. which is calculated by Equation (27). The geometric parameters of the flat diaphragm are the same as those listed in Table 5 .…”
Section: Actuation Of Stress-reduced Corrugated Diaphragmmentioning
confidence: 99%
See 1 more Smart Citation